PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Nurulfajri Nurulfajri (UNIVERSITAS HAMZANWADI, 2016)
abstract: The purpose of this study is conducted to determine the eff ect Model Based Learning Project (Pr oject Based Learning) on Creative Thinking Ability in Class VII MTs Nurussalam Tetebatu Learning Year 2014/2015 thus exp ected to be used as reference material when teaching in schools by teachers and as a guideline for other researchers for a similar study in more depth. This research w as Quasi-Experimental Design with the for m design pretest-posttest control group . This research was taken place at MTs Nuru ssalam Tetebatu in May 2015. The population of this research was all students of the VII MTs Nurussalam Tetebatu utilizing simple random sampling techniq ue in gaining the data. 24 students wer e taken as the experiment class and 25 stud ents were for the control class. The dat a collection used was analysis ability data that was evaluated trough instrument consisted of 8 questions. The data analysis use d was normality test, homogeneity te st, mean score, and t-test for students’ creative thinking ability. The research rasult showed that in the eksperiment class, the mean score was 71.7 and the mean score of the control class was 66.2. The hypothesis test was conducted at the experiment class using t-test. Based on t-te st, the t-count = 10,37 in significant rank 5% and the t-table 2,069 (t-count t-tab le). It means the Ho was rejected and the Ha was accepted, so the hypothesis was accepted.